9 Charting the 'new normal' in Canadian community pharmacy practice: scoping review. (29th July 2022) - Sears, K; Rodgers, J; Barker, JR; Godfrey, C; Pozzobon, L
Abstract : Introduction: To identify the Canada-wide changes in community pharmacy practice in response to the COVID-19 pandemic and to assess what is currently being practiced. What are the emerging practices and regulations that keep community pharmacies safe (customers and professionals) during the COVID-19 pandemic and what are the implications of these changes? Methods: Review includes primary studies (i.e., experimental, quasi-experimental, observational, and qualitative study designs) and grey literature that broadly focused on policies, regulations, and recommendations developed for Canadian community pharmacies during the COVID-19 pandemic. Study abstracts and full texts were screened for eligibility by two reviewers, independently. Data extraction of relevant studies were also done independently by two reviewers. All discrepancies were addressed through further discussion or adjudicated by a third reviewer. Presentation of the extracted data focuses on descriptive frequencies and thematic analysis and the results are presented in diagrammatic or tabular form, with a narrative summary of the findings. Results: Team members screened fifty-five citations and considered five to meet the inclusion criteria, with an additional 449 grey literature items. Pharmacists rely on regulatory and professional associations as their primary information source, yet corporate employers were found to offer better resources for communicating policies to pharmacists. 1 In the pan-Canadian context, Health Canada granted pharmacists new permissions for prescribing, including extending and renewing prescriptions 2 3 while simultaneously recommending that pharmacists should limit patient medication supplies. 2 4 Although COVID-19 updates were regularly being sent by regulatory bodies and national associations, pharmacists were either unaware of where to find or did not understand available information. 1 2 4 5 Discussion: As Canada emerges from the COVID-19 pandemic, there is a 'new normal' for community pharmacy practice, or an expanded role in the overall healthcare system. This review adds to the understanding of how pharmacies faced challenges of incorporating rapidly evolving information into practice, while maintaining client care and worker safety. References: Austin Z, Gregory P. Resilience in the time of pandemic: the experience of community pharmacists during COVID-19. Research in Social and Administrative Pharmacy 2021;17 (1):1867–75. Elbeddini A, Hooda N, Yang L. Role of Canadian pharmacists in managing drug shortage concerns amid the COVID-19 pandemic. Canadian Pharmacists Journal/Revue des Pharmaciens du Canada 2020;153 (4):198–203. Merks P, Jakubowska M, Drelich E, Świeczkowski D, Bogusz J, Bilmin K, et al . The legal extension of the role of pharmacists in light of the COVID-19 global pandemic. Research in Social and Administrative Pharmacy 2021;17 (1):1807–12. Elbeddini A, Botross A, Gerochi R, Gazarin M, Elshahawi A. Pharmacy response to COVID-19: lessons learnt from Canada. Journal of Pharmaceutical Policy and Practice 2020;13 (1):1–8. Gregory PAM, Austin Z. COVID-19: how did community pharmacies get through the first wave? Canadian Pharmacists Journal/Revue des Pharmaciens du Canada 2020;153 (5):243–51.